Advanced Electromagnetic Metamaterials for Temperature Sensing Applications - Ma, Liang; Chen, Dexu; Zheng, Wenxian; Li, Jian; Zahra, Sidrish; Liu, Yifeng; Zhou, Yuedan; Huang, Yongjun; Wen, Guangjun (Frontiers in Physics, 2021)
Metamaterials with novel properties have excite much research attention in the past several decades. Many applications have been proposed and developed for the reported metamaterials in various engineering areas. Especially for the resonant-type metamaterials with narrow resonance linewidth, the resonance frequency and intensity are highly depended on the structure and/or substrate media properties changings induced by the background parameter changings. Therefore different kinds of sensing applications based on the resonant-type metamaterial units or arrays are developed in recent years. In this mini review, we summarize the recently reported sensing, especially the temperature sensing applications, based on different kinds of metamaterial designs. Importantly, by analyzing the advantages and disadvantages of several conventional metamaterial units, the newly proposed high quality-factor metamaterial units are discussed for sensing applications, in terms of the sensitivity and resolution. This mini review can help the researchers in this metamaterial inspired sensor design area to find some new design routes for high-precision sensing.